2014
DOI: 10.1590/1414-431x2014424
|View full text |Cite
|
Sign up to set email alerts
|

A time series analysis of meteorological factors and hospital outpatient admissions for cardiovascular disease in the Northern district of Guizhou Province, China

Abstract: Findings on the effects of weather on health, especially the effects of ambient temperature on overall morbidity, remain inconsistent. We conducted a time series study to examine the acute effects of meteorological factors (mainly air temperature) on daily hospital outpatient admissions for cardiovascular disease (CVD) in Zunyi City, China, from January 1, 2007 to November 30, 2009. We used the generalized additive model with penalized splines to analyze hospital outpatient admissions, climatic parameters, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Our results are in line with some previous studies in Japan 15,16,21 and elsewhere. 14 A population-based study in Japan, 16 in the second-highest quintile was significantly lower (Q4: 0.80, 95% CI 0.69-0.94) for ischemic stroke. This association prevailed through the minimum and maximum temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…Our results are in line with some previous studies in Japan 15,16,21 and elsewhere. 14 A population-based study in Japan, 16 in the second-highest quintile was significantly lower (Q4: 0.80, 95% CI 0.69-0.94) for ischemic stroke. This association prevailed through the minimum and maximum temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…There are 11 inner-city areas in Zunyi: Laocheng (LC) Road, Wangli (WL) Road, Zhonghua (ZH) Road, Nanmenguan (NMG) Road, Yanan (YA) Road, Zhoushuiqiao (ZSQ) Road, Zhongshan (ZS) Road, Beijing (BJ) Road, Shanghai (SH) Road, Xima (XM) Road, and Dalian (DL) Road, covering a wide range of geographic areas in Zunyi city (105 km 2 ) and a total population of more than 110 million. These 11 inner-city areas are homogeneous in terms of lifestyle, education, employment and income, housing, geographical origin of the residents, and effects of air pollution ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Seasonal changes of temperature promote alterations in respiratory morbidity and in total and cause-specifi c mortality. Our previous study found that seasonal changes in Zunyi were associated with residents' respiratory [5,9] and cardiovascular morbidity [18], including asthma and asthma-related symptoms. Moreover, our exploratory study has revealed a linear relationship between respiratory outcomes and daily mean air temperature.…”
Section: Difference In the Prevalence Of Adult Asthma And Asthma-relamentioning
confidence: 99%